Key Stressors Leading to Construction Professionals' Stress in the Gaza Strip, Palestine - Enshassi, Adnan; Swaity, Eman Al. (Penerbit Universiti Sains Malaysia, 2015)
The aim of this paper is to investigate the key stressors that lead to stress among professionals on construction projects. A total of 320 questionnaires were randomly distributed to construction professionals in the Gaza Strip, and 183 were returned, yielding a 51% response rate. Exploratory factor analysis was employed to explore the interrelationships among stressor attributes in four stressor groups (task, personal, physical, and organisational). The results of this study indicated that personality and home-work conflicts are the most prevailing personal stressors linked to stress experienced by Gaza Strip construction professionals. This type of stress was induced because construction professionals did not give attention to their personal lives in addition to their jobs. Task stressors resulted from two types of work overload: quantitative and qualitative. Quantitative overload came from working for long hours with too much work, whereas qualitative overload resulted from a wide range of responsibilities. Physical stressors were not recognised by Gaza Strip construction professionals as an important source of stress. With regard to organisational stressors, it was found that the policies, treatment, and rewards were inadequate. A politicised environment and lack of feedback from the supervisor were responsible for organisational structure stressors. This study will add value to the existing body of knowledge concerning Palestinian professionals' perspectives of stressors in the construction industry. Professionals can take key stressors into consideration to manage and minimise stress on construction projects. Therefore, training sessions on managing and coping with stress is recommended for construction professionals.